Fluorescent asymmetric bis-ureas for pyrophosphate recognition in pure water. Issue 7 (14th January 2016) - Casula, Arianna; Bazzicalupi, Carla; Bettoschi, Alexandre; Cadoni, Enzo; Coles, Simon J.; Horton, Peter N.; Isaia, Francesco; Lippolis, Vito; Mapp, Lucy K.; Marini, Giada M.; Montis, Riccardo; Scorciapino, Mariano Andrea; et al.
Abstract : Fluorescent asymmetric bis-ureas are able to recognize HPpi 3− in water. Abstract : Three fluorescent asymmetric bis-urea receptors (L1–L3 ) have been synthesised. The binding properties ofL1–L3 towards different anions (fluoride, acetate, hydrogencarbonate, dihydrogen phosphate, and hydrogen pyrophosphate HPpi 3− ) have been studied by means of 1 H-NMR, UV-Vis and fluorescence spectroscopy, single crystal X-ray diffraction, and theoretical calculations. In particular, a remarkable affinity for HPpi 3− has been observed in the caseL1 (DMSO- d 6 /0.5% H2 O) which also acts as a fluorimetric chemosensor for this anion. Interestingly, whenL1 is included in cetyltrimethylammonium (CTAB) micelles, hydrogen pyrophosphate recognition can also be achieved in pure water.